Production process of high-purity acetonitrile solvent
Through the process of combining ozone oxidation and impurity removal and composite adsorbent, the problem of impurities in industrial acetonitrile affecting the purity of the impurities is solved, and the production of high-purity acetonitrile is achieved, the process is simplified and energy consumption is reduced.
Patent Information
- Application Number
- CN202510044957.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, industrially produced acetonitrile is easily mixed with various impurities, which makes it difficult to improve the purity, and the purification process is complex and the energy consumption is high, resulting in a low recovery rate of acetonitrile.
The ozone oxidation and impurity removal technology and composite adsorbent are used to remove impurities in the raw materials through the ozone oxidation tower, and then the activated composite adsorbent is used for adsorption, and finally the complete reflux distillation is carried out through the distillation tower to obtain high-purity acetonitrile.
It effectively removes impurities from raw materials, improves the purity of acetonitrile, simplifies the purification process, reduces energy consumption, and improves the recovery rate of acetonitrile.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic raw material production, and in particular to a production process of a high-purity acetonitrile solvent. Background Art
[0002] High-purity (preparative grade) acetonitrile is a high-purity acetonitrile product, mainly used in laboratory research, drug synthesis, separation and purification of impurities and other applications. Acetonitrile (CH3CN) is a colorless liquid with a special odor and is soluble in water and a variety of organic solvents. The purity of preparative-grade acetonitrile is usually very high to meet the needs of laboratory and industrial applications. Its low impurity content, low evaporation residue and excellent batch stability make it suitable for large-scale production. In addition, preparative-grade acetonitrile also has the characteristics of low UV absorption and low moisture content, ensuring high signal sensitivity and good sample stability, making it perform well in applications such as ultraviolet spectroscopy and liquid chromatography that require highly sensitive detection methods, ensuring the accuracy and reliability of the test results, and further improving its applicability in reaction systems that require strict control of moisture content.
[0003] In the prior art, industrial acetonitrile is easily mixed with various impurities, such as moisture, acrylonitrile, hydrocyanic acid, etc. The presence of these impurities can have a strong impact on the purity of acetonitrile, and it is necessary to adopt a complicated purification process, often including steps such as multiple distillations, extractions, adsorptions, etc. In addition, some impurities such as acrylonitrile are similar to the chemical properties between acetonitrile, and it is difficult to separate by simple physical or chemical methods, which further increases the difficulty of purity improvement. Meanwhile, in the production process of preparing grade acetonitrile in technical grade acetonitrile, due to the complex purification process and high energy consumption, the recovery rate of acetonitrile is often lower, and the interaction between some impurities and acetonitrile causes part of acetonitrile to be converted into other substances in the purification process, which cannot be recovered. Summary of the invention
[0004] In order to solve the problems mentioned in the above background technology, the present invention provides a production process of high-purity acetonitrile solvent.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A production process of a high-purity acetonitrile solvent comprises the following steps: S1. The acetonitrile raw material is passed from the tank area to the oxidation tower, and the temperature and feed flow rate of the tank area are controlled. After the material is distributed by the distributor in the tower, it is reversely contacted with the ozone generated by the oxygen source ozone generator in the tower to oxidize and remove impurities from the trace components in the raw material. The distributor in the oxidation tower is a multi-layer spray type. The ozone is obtained by electrochemical treatment of oxygen molecules in or around the electric field by high-voltage ionization using an ozone generator to obtain an oxidized material; S2. The adsorption tower is activated by nitrogen purge in advance, the composite adsorbent is filled in the tower, the oxide material is passed into the adsorption tower, heated to 110-120℃ and maintained for 2-3h, and then purged with nitrogen to room temperature at a purge rate of 40-50m 3 / h, to obtain the adsorbed material; S3, preheat the distillation tower to 75-80 ° C, pass the adsorbed material into the distillation tower, start full reflux operation, control the heating rate, until the top temperature reaches the boiling point of acetonitrile, full reflux for 3-4 hours, when the top temperature is stable at 81-82 ° C, and the acetonitrile purity is ≥99.9% when sampled and analyzed, the finished product is started, acetonitrile is condensed and recovered, and the remaining gas is sent to the combustion furnace for combustion treatment. After the bottom liquid of the tower is cooled to room temperature, it is pumped to the acetonitrile head and tail material storage tank.
[0006] Furthermore, in step S1, the temperature of the tank area is 15-25°C, and the feed flow rate is 480-500 L / h.
[0007] Furthermore, in step S1, the high-pressure ionization parameter of the ozone generator is 30 g / h, and the oxidation treatment time is 4-6 h.
[0008] Furthermore, in step S2, the activation temperature is 150-155° C., and the activation time is 1-2 h.
[0009] Furthermore, the composite adsorbent in step S2 is prepared by the following steps: A1. Under nitrogen protection, toluene and cis-3-hexenyl acetate were added to a reaction kettle, methacrylic acid was added dropwise, and the mixture was stirred until uniformly mixed. A reflux device was installed, concentrated sulfuric acid and p-toluenesulfonic acid were added, and the mixture was heated to 80-90° C. and stirred at a speed of 50-100 rpm for 2-4 hours. After the reaction was completed, the mixture was cooled to room temperature, poured into methanol for precipitation, and filtered to obtain polymethyl methacrylate-cis-3-hexenyl acetate; A2, adding polyvinyl pyrrolidone to a reaction kettle pre-filled with methanol and water, heating to 70-75°C, stirring until the solution is transparent, adding polymethyl methacrylate-cis-3-hexenyl acetate, ethylene glycol dimethacrylate and azobisisobutyronitrile, heating to 80-85°C, reacting for 6-8h, stirring once every 30min, each stirring for 5min, after the reaction is completed, transferring the reaction solution to a centrifuge, centrifuging at 7000-8000rpm for 10-15min, collecting cross-linked microspheres, washing with methanol several times, to obtain cross-linked microspheres; A3. Add bentonite to water, stir at a speed of 200-300 rpm for 20-30 min, adjust the pH value to 7.0±0.1 to obtain a bentonite suspension, add cross-linked microspheres to the bentonite suspension, ultrasonically treat for 5-10 min to obtain a composite suspension, dry the composite suspension through a spray dryer, set the inlet temperature to 150-160° C., and the outlet temperature to 80-90° C., and collect to obtain a composite absorbent.
[0010] Furthermore, in step S3, the reflux ratio in the total reflux is 3:1, the heating rate during total reflux is 1°C per 10 min, the extraction rate is 300-400 L / h, and the pressure in the tower is maintained at 0.04-0.05 MPa.
[0011] Furthermore, in step A1, the feed mass ratio of toluene, 3-hexenyl cis-acetic acid, methacrylic acid, concentrated sulfuric acid and p-toluenesulfonic acid is 200:(12-15):(18-22):(1-3):(0.5-1).
[0012] Furthermore, in step A2, the mass ratio of polyvinyl pyrrolidone, methanol, water, polymethyl methacrylate-3-hexenyl cis-acetate, ethylene glycol dimethacrylate and azobisisobutyronitrile is (8-10):100:300:(13-15):(1.5-4):(0.25-0.5).
[0013] Furthermore, in step A3, the feed mass ratio of bentonite to water is (10-12):100, and the feed mass ratio of cross-linked microspheres to bentonite suspension is (20-25):(80-100).
[0014] Beneficial effects of the present invention: 1. In the technical solution of the present invention, toluene and cis-3-hexenol acetate are mixed with methacrylic acid, and an esterification reaction occurs through the catalytic action of concentrated sulfuric acid and p-toluenesulfonic acid, and methacrylic acid is esterified with the hydroxyl of cis-3-hexenol acetate to form polymethyl methacrylate-cis-3-hexenol acetate. In the presence of polyvinyl pyrrolidone, polymethyl methacrylate-cis-3-hexenol acetate, ethylene glycol dimethacrylate and azobisisobutyronitrile undergo a cross-linking reaction to form cross-linked microspheres with a three-dimensional network structure. Bentonite is dispersed in water to form a suspension, and the surface of bentonite particles is negatively charged by adjusting the pH value to neutral, which is conducive to the combination with the cross-linked microspheres. The cross-linked microspheres are added to the bentonite suspension, and the two are fully mixed and combined by ultrasonic treatment. Ultrasonic treatment can destroy the local tension in the liquid and promote the uniform dispersion and combination of microspheres and bentonite particles. Bentonite and cross-linked microspheres have a porous structure and a high specific surface area, which can provide a large number of adsorption sites, and the target molecules are adsorbed on the surface or in the pores by physical adsorption. The functional groups in the cross-linked microspheres react chemically with the target molecules to form chemical bonds or hydrogen bonds, further enhancing the adsorption effect.
[0015] 2. In the technical solution of the present invention, by controlling the temperature and feed flow rate of the tank area and using ozone to oxidize and remove trace components in the raw materials, impurities and harmful substances in the raw materials are effectively removed. Ozone, as a strong oxidant, can react with reducing substances in the raw materials and oxidize them into products that are easy to remove, thereby improving the purity of the raw materials. At the same time, the multi-layer spray-type distributor in the oxidation tower ensures sufficient contact and reaction between the raw materials and ozone, thereby improving the oxidation efficiency. DETAILED DESCRIPTION
[0016] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] Unless otherwise specified, the raw materials used in the present invention are all conventional products purchased from the market.
[0018] Preparation Example 1 The composite adsorbent comprises the following steps to prepare: A1. Under nitrogen protection, 200 kg of toluene and 12 kg of cis-3-hexenol acetate were added to a reactor, 18 kg of methacrylic acid was added dropwise, stirred until uniformly mixed, a reflux device was installed, 1 kg of 98% concentrated sulfuric acid and 0.5 kg of p-toluenesulfonic acid were added, heated to 80 ° C, stirred at a speed of 50 rpm for 2 h, and after the reaction was completed, cooled to room temperature, poured into methanol for precipitation, and filtered to obtain polymethyl methacrylate-cis-3-hexenyl acetate; A2, 8kg of polyvinyl pyrrolidone was added to a reactor pre-loaded with 100kg of methanol and 300kg of water, heated to 70°C, stirred until the solution was transparent, 13kg of polymethyl methacrylate-cis-3-hexenyl acetate, 1.5kg of ethylene glycol dimethacrylate and 0.25kg of azobisisobutyronitrile were added, the temperature was raised to 80°C, and the reaction was carried out for 6h, during which the mixture was stirred every 30min for 5min each time. After the reaction was completed, the reaction solution was transferred to a centrifuge and centrifuged at 7000rpm for 10min, the cross-linked microspheres were collected, and washed several times with methanol to obtain cross-linked microspheres; A3. Add 10 kg of bentonite to 100 kg of water, stir at 200 rpm for 20 min, adjust the pH value to 7.0 to obtain a bentonite suspension, add 20 kg of cross-linked microspheres to 80 kg of the bentonite suspension, ultrasonically treat for 5 min to obtain a composite suspension, dry the composite suspension through a spray dryer, set the inlet temperature to 150 ° C, the outlet temperature to 80 ° C, and collect to obtain a composite absorbent.
[0019] Preparation Example 2 The composite adsorbent comprises the following steps to prepare: A1. Under nitrogen protection, 200 kg of toluene and 12.5 kg of cis-3-hexenol acetate were added to a reactor, 20 kg of methacrylic acid was added dropwise, stirred until uniformly mixed, a reflux device was installed, 2 kg of 98% concentrated sulfuric acid and 0.75 kg of p-toluenesulfonic acid were added, heated to 85 ° C, stirred at a speed of 60 rpm for 3 h, and after the reaction was completed, cooled to room temperature, poured into methanol for precipitation, filtered, and polymethyl methacrylate-cis-3-hexenyl acetate was obtained; A2, 9 kg of polyvinyl pyrrolidone was added to a reactor pre-loaded with 100 kg of methanol and 300 kg of water, heated to 72 ° C, stirred until the solution was transparent, 14 kg of polymethyl methacrylate-cis-3-hexenyl acetate, 2 kg of ethylene glycol dimethacrylate and 0.4 kg of azobisisobutyronitrile were added, the temperature was raised to 82 ° C, and the reaction was carried out for 7 hours, during which the mixture was stirred every 30 minutes for 5 minutes each time. After the reaction was completed, the reaction solution was transferred to a centrifuge and centrifuged at 7500 rpm for 12 minutes, the cross-linked microspheres were collected, and washed several times with methanol to obtain cross-linked microspheres; A3. Add 11 kg of bentonite to 100 kg of water, stir at 250 rpm for 25 min, adjust the pH value to 7.0 to obtain a bentonite suspension, add 22.5 kg of cross-linked microspheres to 90 kg of the bentonite suspension, ultrasonically treat for 7 min to obtain a composite suspension, dry the composite suspension through a spray dryer, set the inlet temperature to 155 ° C, the outlet temperature to 85 ° C, and collect to obtain a composite absorbent.
[0020] Preparation Example 3 The composite adsorbent comprises the following steps to prepare: A1. Under nitrogen protection, 200 kg of toluene and 15 kg of cis-3-hexenol acetate were added to a reactor, 22 kg of methacrylic acid was added dropwise, stirred until uniformly mixed, a reflux device was installed, 3 kg of 98% concentrated sulfuric acid and 1 kg of p-toluenesulfonic acid were added, heated to 90 ° C, stirred at a speed of 100 rpm for 4 hours, and after the reaction was completed, the reaction was cooled to room temperature, poured into methanol for precipitation, and filtered to obtain polymethyl methacrylate-cis-3-hexenyl acetate; A2, 10kg of polyvinyl pyrrolidone was added to a reactor pre-loaded with 100kg of methanol and 300kg of water, heated to 75°C, stirred until the solution was transparent, 15kg of polymethyl methacrylate-cis-3-hexenyl acetate, 4kg of ethylene glycol dimethacrylate and 0.5kg of azobisisobutyronitrile were added, the temperature was raised to 85°C, and the reaction was carried out for 8h, during which the mixture was stirred every 30min for 5min each time. After the reaction was completed, the reaction solution was transferred to a centrifuge and centrifuged at 8000rpm for 15min, the cross-linked microspheres were collected, and washed several times with methanol to obtain cross-linked microspheres; A3. Add 12 kg of bentonite to 100 kg of water, stir at 300 rpm for 30 min, adjust the pH value to 7.0 to obtain a bentonite suspension, add 25 kg of cross-linked microspheres to the 100 kg bentonite suspension, ultrasonically treat for 10 min to obtain a composite suspension, dry the composite suspension through a spray dryer, set the inlet temperature to 160 ° C, the outlet temperature to 90 ° C, and collect to obtain a composite absorbent. Example 1
[0021] A production process of a high-purity acetonitrile solvent comprises the following steps: S1. The industrial-grade acetonitrile raw material is passed from the tank area into the oxidation tower, the temperature of the tank area is controlled to be 15°C, the feed flow rate is 480L / h, the material is distributed by the distributor in the tower, and then it is reversely contacted with the ozone generated by the ozone generator in the tower, the high-pressure ionization parameter is 30g / h, and the oxidation treatment time is 4h to obtain the oxidized material; S2, the adsorption tower was activated by nitrogen purge in advance, the activation temperature was 150 ° C, the activation time was 1 h, 300 kg of the composite adsorbent prepared in Example 1 was filled in the tower, the oxide material was passed into the adsorption tower, heated to 110 ° C and maintained for 2 h, and then purged with nitrogen to room temperature to obtain the adsorbed material; S3. Preheat the distillation tower to 75°C, pass the adsorbed material into the distillation tower, start full reflux operation, the reflux ratio is 3:1, the heating rate is 1°C every 10 minutes, the extraction rate is 300L / h, and the pressure in the tower is maintained at 0.04MPa until the top temperature reaches the boiling point of acetonitrile. When the top temperature is stabilized at 81°C and the purity of acetonitrile is ≥99.9% after sampling and analysis, start to extract the finished product and condense to obtain high-purity acetonitrile. Example 2
[0022] A production process of a high-purity acetonitrile solvent comprises the following steps: S1. The industrial-grade acetonitrile raw material is passed from the tank area into the oxidation tower, the temperature of the tank area is controlled to be 20°C, the feed flow rate is 490L / h, the material is distributed by the distributor in the tower, and then it is reversely contacted with the ozone generated by the ozone generator in the tower, the high-pressure ionization parameter is 30g / h, and the oxidation treatment time is 5h to obtain the oxidized material; S2, the adsorption tower was activated by nitrogen purge in advance, the activation temperature was 152 ° C, the activation time was 1.5 h, 350 kg of the composite adsorbent prepared in Example 2 was filled in the tower, the oxide material was passed into the adsorption tower, heated to 115 ° C and maintained for 2.5 h, and then purged with nitrogen to room temperature to obtain the adsorbed material; S3, preheat the distillation tower to 77 ° C, pass the adsorbed material into the distillation tower, start full reflux operation, the reflux ratio is 3:1, the heating rate is 1 ° C every 10 minutes, the extraction rate is 350L / h, and the pressure in the tower is maintained at 0.045MPa until the top temperature reaches the boiling point of acetonitrile. When the top temperature is stabilized at 81.5 ° C and the purity of acetonitrile is ≥99.9% after sampling and analysis, the finished product is started to be extracted and condensed to obtain high-purity acetonitrile. Example 3
[0023] A production process of a high-purity acetonitrile solvent comprises the following steps: S1. The industrial-grade acetonitrile raw material is passed from the tank area into the oxidation tower, the temperature of the tank area is controlled to be 25°C, the feed flow rate is 500L / h, the material is distributed by the distributor in the tower, and then it is reversely contacted with the ozone generated by the ozone generator in the tower, the high-pressure ionization parameter is 30g / h, and the oxidation treatment time is 6h to obtain the oxidized material; S2, the adsorption tower was activated by nitrogen purge in advance, the activation temperature was 155 ° C, the activation time was 2h, 400kg of the composite adsorbent prepared in Example 3 was loaded into the tower, the oxide material was passed into the adsorption tower, heated to 120 ° C and maintained for 3h, and then purged with nitrogen to room temperature to obtain the adsorbed material; S3, preheat the distillation tower to 80 ° C, pass the adsorbed material into the distillation tower, start full reflux operation, the reflux ratio is 3:1, the heating rate is 1 ° C every 10 minutes, the extraction rate is 400L / h, and the pressure in the tower is maintained at 0.05MPa until the top temperature reaches the boiling point of acetonitrile. When the top temperature is stabilized at 82 ° C and the purity of acetonitrile is ≥99.9% after sampling and analysis, the finished product is started to be extracted and condensed to obtain high-purity acetonitrile.
[0024] Comparative Example 1 The difference between this comparative example and Preparation Example 1 is that cis-3-hexenol acetate is not added, and the other steps are the same as those in Preparation Example 1.
[0025] Comparative Example 2 The difference between this comparative example and Preparation Example 2 is that methacrylic acid is not added, and the other steps are the same as Preparation Example 2.
[0026] Comparative Example 3 The difference between this comparative example and Preparation Example 3 is that polyvinyl pyrrolidone is not added, and the other steps are the same as Preparation Example 3.
[0027] Comparative Example 4 The difference between this comparative example and Example 1 is that the adsorbent prepared in Comparative Example 1 is used, and the other steps are the same as those in Example 1.
[0028] Comparative Example 5 The difference between this comparative example and Example 2 is that the adsorbent prepared in Comparative Example 2 is used, and the other steps are the same as those in Example 2.
[0029] Comparative Example 6 The difference between this comparative example and Example 3 is that the adsorbent prepared in Comparative Example 3 is used, and the other steps are the same as those in Example 3.
[0030] Referring to the method in T / CSTM 00239-2020 "Chemical Reagent Preparation Grade Acetonitrile", the acetonitrile prepared in Examples 1-3 and Comparative Examples 4-6 was tested, and the results are shown in Table 1: Table 1. Acetonitrile test results of Examples 1-3 and Comparative Examples 4-6 serial number Example 1 Example 2 Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Acetonitrile content (%) 99.97 99.96 99.96 98.73 98.76 98.87 Chroma / Hazen Unit 4 4 4 5 4 5 Moisture (%) 0.009 0.009 0.008 0.016 0.017 0.012 Evaporation residue (mg / kg) 0.24 0.23 0.21 0.96 0.91 1.24 <![CDATA[Acidity (calculated as H + in mmol / g)]]> 0.001 0.001 0.001 0.002 0.002 0.003 <![CDATA[Alkalinity (calculated as OH - , mmol / g)]]> 0.0002 0.0002 0.0002 0.0002 0.0002 0.0002 Absorbance (190nm) 0.6 0.7 0.7 0.9 0.9 1.1 Absorbance (200nm) 0.08 0.08 0.8 0.11 0.12 0.12 Absorbance (220nm) 0.01 0.01 0.01 0.06 0.06 0.06 As can be seen from Table 1, the acetonitrile content of Examples 1-3 is higher than 99.9%, while Comparative Examples 4-6 are significantly lower than this level. The adsorbent used in the comparative examples may cause its adsorption capacity for impurities in acetonitrile to decrease due to the lack of some components, thereby affecting the purity of acetonitrile. The chromaticity of Examples 1-3 is 4, while the chromaticity of Comparative Examples 4 and 6 is slightly higher. The difference in chromaticity may be due to the different adsorption capacity of the adsorbent for colored impurities. The adsorbents in Comparative Examples 4 and 6 may not be able to effectively adsorb colored impurities. The moisture content of Examples 1-3 is lower than 0.01%, while the moisture content of Comparative Examples 4-6 is higher. The performance difference of the adsorbent may lead to different adsorption capacity for moisture. In addition, the temperature, pressure and other conditions during the adsorption and distillation process may also affect the removal effect of moisture. The evaporation residue content of Example 1-3 is much lower than that of Comparative Examples 4-6. The evaporation residue mainly comes from impurities that are not completely evaporated. The adsorbent used in the comparative example may not be able to effectively remove these impurities due to poor performance. The acidity and alkalinity of Examples 1-3 are both low, while the acidity of Comparative Examples 4-6 is slightly higher. The difference in acidity and alkalinity may be due to the different adsorption capacities of the adsorbents for acidic and basic impurities. In addition, the temperature, time and other conditions during the adsorption process may also affect the removal effect of the acidity and alkalinity. At all detection wavelengths, the absorbance of Examples 1-3 is lower than that of Comparative Examples 4-6. The difference in absorbance reflects the different impurity contents in the samples. Due to poor performance, the adsorbent used in the comparative example may not be able to effectively remove these impurities that absorb at specific wavelengths.
[0031] In summary, the composite adsorbent prepared in Preparation Examples 1-3 exhibits a significant adsorption effect in the production of high-purity acetonitrile solvent, so that the high-purity acetonitrile solvent prepared in Examples 1-3 has a higher purity.
[0032] In the description of the specification, the description with reference to the terms "embodiment", "various embodiments" and the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or preparation example are included in at least one embodiment or preparation example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or preparation example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or preparation examples in a suitable manner.
[0033] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A production process for a high-purity acetonitrile solvent, characterized in that: The following steps are involved: S1. The acetonitrile raw material is passed from the tank area into the oxidation tower, and the temperature and feed flow rate of the tank area are controlled. After the material is distributed by the distributor in the tower, it is reversely contacted with the ozone generated by the ozone generator in the tower to obtain the oxidized material; S2, the adsorption tower is activated by nitrogen purge in advance, the composite adsorbent is filled in the tower, the oxide material is passed into the adsorption tower, heated to 110-120°C for 2-3h, and then purged with nitrogen to room temperature to obtain the adsorbed material; S3. Preheat the distillation tower to 75-80°C, pass the adsorbed material into the distillation tower, and start full reflux operation until the top temperature reaches the boiling point of acetonitrile. When the top temperature is stabilized at 81-82°C and the purity of acetonitrile is ≥99.9% after sampling and analysis, start to take out the finished product and condense to obtain high-purity acetonitrile.
2. A production process for a high-purity acetonitrile solvent according to claim 1, characterized in that, In step S1, the temperature of the tank area is 15-25°C, and the feed flow rate is 480-500L / h.
3. A production process for a high-purity acetonitrile solvent according to claim 1, characterized in that: The high-pressure ionization parameter of the ozone generator in step S1 is 30 g / h, and the oxidation treatment time is 4-6 h.
4. A production process for a high-purity acetonitrile solvent according to claim 1, characterized in that: The activation temperature in step S2 is 150-155° C., and the activation time is 1-2 h.
5. A production process for a high-purity acetonitrile solvent according to claim 1, characterized in that: The composite adsorbent in step S2 is prepared by the following steps: A1. Under nitrogen protection, toluene and cis-3-hexenyl acetate were added to a reaction kettle, methacrylic acid was added dropwise, and the mixture was stirred until uniformly mixed. A reflux device was installed, concentrated sulfuric acid and p-toluenesulfonic acid were added, and the mixture was heated to 80-90° C. and stirred at a speed of 50-100 rpm for 2-4 hours. After the reaction was completed, the mixture was cooled to room temperature, poured into methanol for precipitation, and filtered to obtain polymethyl methacrylate-cis-3-hexenyl acetate; A2, adding polyvinyl pyrrolidone to a reaction kettle pre-filled with methanol and water, heating to 70-75°C, stirring until the solution is transparent, adding polymethyl methacrylate-cis-3-hexenyl acetate, ethylene glycol dimethacrylate and azobisisobutyronitrile, heating to 80-85°C, reacting for 6-8h, stirring once every 30min, each stirring for 5min, after the reaction is completed, transferring the reaction solution to a centrifuge, centrifuging at 7000-8000rpm for 10-15min, collecting cross-linked microspheres, washing with methanol several times, to obtain cross-linked microspheres; A3. Add bentonite to water, stir at a speed of 200-300 rpm for 20-30 min, adjust the pH value to 7.0±0.1 to obtain a bentonite suspension, add cross-linked microspheres to the bentonite suspension, ultrasonically treat for 5-10 min to obtain a composite suspension, dry the composite suspension through a spray dryer, set the inlet temperature to 150-160° C., and the outlet temperature to 80-90° C., and collect to obtain a composite absorbent.
6. A production process for a high-purity acetonitrile solvent according to claim 1, characterized in that: The reflux ratio in the total reflux in step S3 is 3:1, the heating rate during total reflux is 1°C per 10 min, the extraction rate is 300-400 L / h, and the pressure in the tower is maintained at 0.04-0.05 MPa.
7. A production process for a high-purity acetonitrile solvent according to claim 1, characterized in that: In step A1, the feed mass ratio of toluene, 3-hexenyl cis-acetic acid, methacrylic acid, concentrated sulfuric acid and p-toluenesulfonic acid is 200:(12-15):(18-22):(1-3):(0.5-1).
8. A production process for a high-purity acetonitrile solvent according to claim 1, characterized in that: In step A2, the mass ratio of polyvinyl pyrrolidone, methanol, water, polymethyl methacrylate-3-hexenyl cis-acetate, ethylene glycol dimethacrylate and azobisisobutyronitrile is (8-10):100:300:(13-15):(1.5-4):(0.25-0.5).
9. A production process for a high-purity acetonitrile solvent according to claim 1, characterized in that: In step A3, the feed mass ratio of bentonite to water is (10-12):100, and the feed mass ratio of cross-linked microspheres to bentonite suspension is (20-25):(80-100).
Citation Information
Patent Citations
High-purity acetonitrile and method and device for preparing high-purity acetonitrile
CN104058994A
Production process of chromatographic grade acetonitrile
CN119176767A